2021
DOI: 10.1002/jcsm.12804
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota and short‐chain fatty acid alterations in cachectic cancer patients

Abstract: Background Cancer cachexia is characterized by a negative energy balance, muscle and adipose tissue wasting, insulin resistance, and systemic inflammation. Because of its strong negative impact on prognosis and its multifactorial nature that is still not fully understood, cachexia remains an important challenge in the field of cancer treatment. Recent animal studies indicate that the gut microbiota is involved in the pathogenesis and manifestation of cancer cachexia, but human data are lacking. The present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 40 publications
3
60
0
Order By: Relevance
“…Megamonas and Akkermansia showed significantly higher abundance in both the NC and BN groups. Ubachs et al (2021) demonstrated that Megamonas was decreased in the feces of cachectic cancer patients; in recurrent pancreatic tumor tissues, Akkermansia was decreased (Jeong et al, 2020). Additionally, Ren et al (2020) developed the nanoparticle NpRg3 to inhibit hepatocellular carcinoma development and metastasis by elevating the abundance of Verrucomicrobia.…”
Section: Discussionmentioning
confidence: 99%
“…Megamonas and Akkermansia showed significantly higher abundance in both the NC and BN groups. Ubachs et al (2021) demonstrated that Megamonas was decreased in the feces of cachectic cancer patients; in recurrent pancreatic tumor tissues, Akkermansia was decreased (Jeong et al, 2020). Additionally, Ren et al (2020) developed the nanoparticle NpRg3 to inhibit hepatocellular carcinoma development and metastasis by elevating the abundance of Verrucomicrobia.…”
Section: Discussionmentioning
confidence: 99%
“…[ 33 , 35 ]. Recently, two clinical studies detected the compositional differences in GM between two small cohorts of NSCLC patients with and without cancer cachexia [ 36 , 37 ]. Consistent with these studies, in our large cohort of NSCLC, we did not observe any differences in alpha diversity.…”
Section: Discussionmentioning
confidence: 99%
“…A study has found that butyrate could inhibit proliferation of lung cancer by modulating p21 expression, and propionate could inhibit cell growth by inducing cell apoptosis and cell cycle arrest ( Kim et al., 2019 ). In addition, a recent study reported that SCFAs tended to be lower in cachectic cancer patients, which indicated that SCFAs may be crucial for clinical nutrition in cancer patients ( Ubachs et al., 2021 ). It is known that vancomycin mainly acts on gram-positive bacteria, including some butyrate-producing bacteria, which may lead to SCFA concentrations decreased ( Uribe-Herranz et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%